Unraveling the intricate dance of the Mediterranean diet and gut microbiota in autoimmune resilience - Tsigalou, Christina; Tsolou, Avgi; Stavropoulou, Elisavet; Konstantinidis, Theocharis; Zafiriou, Efterpi; Dardiotis, Efthymios; Tsirogianni, Alexandra; Bogdanos, Dimitrios (Frontiers in Nutrition, 2024)
The nutritional habits regulate the gut microbiota and increase risk of an autoimmune disease. Western diet is rich in sugars, meat, and poly-unsaturated fatty acids, which lead to dysbiosis of intestinal microbiota, disruption of gut epithelial barrier and chronic mucosal inflammation. In contrast, the Mediterranean Diet (MedDiet) is abundant in ω3 fatty acids, fruits, and vegetables, possessing anti-inflammatory properties that contribute to the restoration of gut eubiosis. Numerous studies have extensively examined the impact of MedDiet and its components on both health and various disease states. Additionally, specific investigations have explored the correlation between MedDiet, microbiota, and the risk of autoimmune diseases. Furthermore, the MedDiet has been linked to a reduced risk of cardiovascular diseases, playing a pivotal role in lowering mortality rates among individuals with autoimmune diseases and comorbidities. The aim of the present review is to specifically highlight current knowledge regarding possible interactions of MedDiet with the patterns of intestinal microbiota focusing on autoimmunity and a blueprint through dietary modulations for the prevention and management of disease’s activity and progression.